PENERAPAN SISTEM INFORMASI DESA DAN KAWASAN DI KABUPATEN KLUNGKUNG - Widyantara, I. M. O.; Linawati, Linawati; Mertasana, I. P. A.; Setiawan, W. (Buletin Udayana Mengabdi; Vol 16 No 2 (2017), 2017)
This study aimed to implement the village and region information system applications (SIDeKa) in Klungkung regency, to inform potential profile data of the village and the region, as well as the characteristics of the villagers globally via the internet. The goal was to provide a database of potential village to village-based development planning. Implementation of SIDeKa done with collaboration strategy model, which involves a team of devotion Udayana University, Klungkung regency government, and volunteers of Information Technology (ICT) from Agents of Change in Rural Informatics (API Desa). Service activities aimed at empowering volunteers ICT of API Desa by providing training SIDeKa application. Furthermore, volunteers continued assistance activities to the administrator of the village where the application SIDeKa applied. In general, SIDeKa application training to volunteers ICTs was able to support the implementation of SIDeKa for the dissemination of statistical information potential of each village in Klungkung.